Characteristics and complexity of chronic pain patients referred to a community-based multidisciplinary chronic pain clinic. Issue 1 (1st January 2018) - May, C.; Brcic, V.; Lau, B.
ABSTRACT: Background: Community-based care fills an important service gap for patients living with chronic pain. Better understanding of unmet patient needs in the community may inform improved policy and resource allocation. Aims: The aim of this study was to describe patients presenting to a community-based, multidisciplinary chronic pain clinic in Vancouver, British Columbia. Methods: This is a retrospective cross-sectional study of 935 unique consecutive patients who completed an intake questionnaire between January 2016 and March 2017. All data were patient reported. Results: Nine hundred thirty-five patient records were analyzed for descriptive characteristics. The mean age of the population was 49.5 (SD = 14.9) years; 70% were female. Approximately 50% of patients lived below the poverty line in Vancouver; 30% were not working due to disability, 51% had pain for more than 5 years, and 63% reported severe functional impairment. Conclusions: Substantial unmet need is demonstrated in this patient population accessing a community-based chronic pain clinic. The population described is mainly of working age with significant functional impairment, reflecting a high level of need due to severity and duration of symptoms, poverty, and other characteristics described.